2008
DOI: 10.1111/j.1447-0594.2008.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and sex on progression of carotid intima‐media thickness: A retrospective 6‐year follow‐up study

Abstract: Sex differences exist in the relationship between increases in IMT and age. Age, sex and diabetes mellitus represented the main risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…Previous studies also showed similar results in patients with breast cancer and carcinoma [29,30]. There was also a positive correlation between CIMT and patient age, as reported by previous studies [1,31].…”
Section: Evaluation Of the Effects Of Biochemical Parameters On Cimtsupporting
confidence: 86%
“…Previous studies also showed similar results in patients with breast cancer and carcinoma [29,30]. There was also a positive correlation between CIMT and patient age, as reported by previous studies [1,31].…”
Section: Evaluation Of the Effects Of Biochemical Parameters On Cimtsupporting
confidence: 86%
“…In our study, we mainly discuss the age and sex-specific relationships between carotid IMT and ambulatory BPV. In Takato's retrospective study [31], age and sex had some effects on the increased carotid IMT. IMT increased with age in both men and women, but mean annual increase in IMT increased with age only in man.…”
Section: Discussionmentioning
confidence: 96%
“…Study by Takato et al showed similar results for risk factors age and diabetes. 14 Yilmaz et al in their study observed that IMT was independently associated with CKD stage and mean arterial pressure. 15 Ekart et al found a statistically significant correlation between carotid IMT and the average one-monthly diastolic BP (P < 0.05) and ambulatory BP monitoring (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%